Detection of Burkholderia pseudomallei in Suspected Melioidosis at Universitas Sumatera Utara (USU) Hospital, North Sumatra, Indonesia - R. Lia Kusumawati; Mirzan Hasibuan; Afrinayanti W. Siregar; Cynthia Gozali (Journal of Pure and Applied Microbiology)
Burkholderia pseudomallei, the causative agent of melioidosis, is endemic in Southeast Asia and tropical regions like Indonesia. This bacterium poses a challenge due to its uncommon and resistance to high-generation antibiotics. This study aims to detect B. pseudomallei in clinical samples from patients suspected of having melioidosis and to describe its clinical manifestations. A total of 118 clinical samples were collected and analyzed using Ashdown’s Selective Agar and routine bacteriological media, while the Vitek 2 Compact system was utilized for antibiotic identification and sensitivity testing. B. pseudomallei was detected in 9 (7.6%) samples, with the highest positivity rate in sputum at 6/59 (10.16%), followed by pus at 5.9% (1/17), pleural fluid at 10% (1/10), and bronchoalveolar lavage (BAL) at 4.5% (1/22). No B. pseudomallei growth was detected in blood and urine samples. Clinically, the positive cases exhibited symptoms akin to pulmonary tuberculosis in 3/9 (33%), combined hydropneumothorax and pulmonary TB in 2/9 (22%), and bilateral pleural effusions in 1/9 (11%). Other clinical presentations included a combination of bilateral pleural effusions and pulmonary TB, mediastinal pleural effusion with pulmonary TB and pneumonia, and burns on the soles of the feet. Antibiotic susceptibility testing revealed effective treatment options for ceftazidime, piperacillin-tazobactam, meropenem, and tigecycline. These findings highlight B. pseudomallei as a significant health concern in North Sumatra, emphasizing the need for improved diagnostic awareness and effective antimicrobial strategies to manage melioidosis cases.